2019
DOI: 10.1111/irv.12675
|View full text |Cite
|
Sign up to set email alerts
|

A(H9N2) influenza viruses associated with chicken mortality in outbreaks in Algeria 2017

Abstract: In late 2017, increased mortality was detected in chicken farms in Algeria undergoing A(H9N2) influenza outbreaks. Analysis of viruses isolated from affected farms showed that they were monophyletic, were of the G1 hemagglutinin (HA) lineage, and were antigenically and genetically similar to viruses detected contemporaneously in other countries in Northern Africa and the Middle East. The virus was able to spread via contact transmission between ferrets but did not cause disease in intravenously inoculated chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…Fifteen HA gene sequences of avian influenza virus H9N2 subtype were retrieved from the tissues of dead poultry. Phylogenetic analysis showed that these sequences were closely related to the H9N2 virus sequences reported recently in Morocco and Burkina Faso [193].…”
Section: Algeriasupporting
confidence: 67%
“…Fifteen HA gene sequences of avian influenza virus H9N2 subtype were retrieved from the tissues of dead poultry. Phylogenetic analysis showed that these sequences were closely related to the H9N2 virus sequences reported recently in Morocco and Burkina Faso [193].…”
Section: Algeriasupporting
confidence: 67%
“…Nevertheless, the virus from Benin (Bn/145) showed a decrease of replicative fitness in human cells compared to other African and Asian viruses tested. In vivo characterizations were not performed since closely related viruses from Algeria and Ghana, and the human strain A/Hong Kong/1073/99 had already been characterized in chickens or ferrets [ 12 , 14 , 30 ]. Algerian viruses did not show any increase of virulence or airborne transmission ability in ferrets [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the emergence of G1 lineage H9N2 viruses in Morocco in early 2016, H9N2 viruses have been widely detected in Northern Africa, with spread to Western Africa, suggesting that the circulation of AIVs is markedly changing in the region. LPAI H9N2 viruses have continued to circulate in Morocco and Algeria [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In North Africa, the virus was detected in Tunisia [ 13 ] and recently in Morocco [ 14 ]. However, no official report is available on the circulation of H9N2 viruses in Algeria, except for the recent declaration of one case in the North Center of the country [ 17 ]. Besides, in the province of Batna (Northeast Algeria), an outbreak of highly contagious respiratory disease was reported in broiler flocks, in 2017 and we showed here that the outbreak was due to H9N2 AIV.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jeevan et al, (2019) have reported isolation of H9N2 AIV from an outbreak observed, in 2017, in the Central region of Algeria. Their study focused on phylogenetic characterization and pathogenicity of the isolates in experimental animals [ 17 ]. However, the full-length genome sequence analysis had not been carried out.…”
Section: Introductionmentioning
confidence: 99%